BEHAVIORAL MANAGEMENT AS A FORMS OF SMOKING AND ALCOHOL CONSUMPTION PREVENTION IN ADOLESCENTS - Nildawati Amir; Yudi Adnan (Homes Journal = Hospital Management Studies Journal, 2021)
Background:The prevalence of risk behavior in adolescents is increasing and the impact is very worrying. Various data and facts related to risk behavior in adolescents, namely smoking, drinking alcohol, drug abuse, and premarital sexual relations.Objective:The purpose of this study was to examine more comprehensively related behavioral management as a form of prevention of smoking and alcohol consumption among adolescents in South Sulawesi Province, Indonesia.Method: Qualitative research with a design case study. The informants in this study were adolescents aged 12-24 years who live in South Sulawesi Province, Indonesia (Makassar City, Gowa Regency, Bone Regency, and Sinjai Regency). Result: The main factors causing the behavior of consuming alcohol and smoking are the sense of wanting to try, peer influence, and lack of access to information. Regarding the behavioral management of adolescent risk behavior, it is known that the role of parents, relatives, neighbors, neighborhood communities, peers, and health workers contributes to efforts to prevent smoking and alcohol consumption among adolescents.Conclusion: The contribution of parents is very necessarytosupervise the daily life or behavior of children. The government and health workers are required to be more effective in dealing with the problem of adolescent risk behavior by routinely providing guidance and counseling. The community can play an active role in monitoring adolescents who engage in risky behavior. However, this will not be effective if there is no collaboration between the perpetrators at risk themselves, parents, family, peers, and the neighborhood where they live.